Rare earth slurry for radiant cooling cloth and preparation method thereof

By using raw materials such as aluminum oxide, barium oxide, niobium oxide, rare earth oxide and titanium oxide in rare earth slurry, amorphous materials with high refractive index and introducing barium and titanium elements, the problem of high cost and difficult to uniform performance of radiation refrigeration fabrics in the prior art is solved, and a low-cost and high-performance slurry preparation is achieved.

CN118085612BActive Publication Date: 2025-04-04ZHONGXIN YI TU TECH DEV CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410042063.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-11
Publication Date
2025-04-04
Estimated Expiration
2044-01-11

AI Technical Summary

Technical Problem

The prior art is difficult to unify low cost, low titanium content and high performance in radiation-refrigerated fabrics, which makes it difficult to increase the reflectivity and emissivity of the fabric at the same time, and the cost is also high, affecting market competitiveness.

Method used

A rare earth slurry is used, and its raw materials include aluminum oxide, barium oxide, niobium oxide, rare earth oxide and titanium oxide. It is prepared by high-temperature sintering and cold water quenching to form a high-refractive amorphous material, and further introduce barium and titanium elements to increase the refractive index.

Benefits of technology

It achieves low cost of slurry, window emissivity up to 96%, reflectivity up to 92%, while reducing the production cost of fabrics and improving market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118085612B_ABST
    Figure CN118085612B_ABST
Patent Text Reader

Abstract

The present invention discloses a rare earth slurry for radiative cooling fabrics. The slurry comprises, by weight, 10-25 parts of aluminum oxide, 5-10 parts of barium oxide, 25-36 parts of niobium oxide, 13-20 parts of rare earth oxide, and 16-35 parts of titanium oxide. The slurry of the present invention has low production cost and high window emissivity and reflectivity. It is applied on the surface of fabrics, building exterior walls, roofs, and oil storage tanks to effectively reduce the surface temperature of objects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating materials, and in particular to a rare earth slurry for radiant cooling cloth and a preparation method thereof. Background Art

[0002] With the development of science and technology, clothing thermal energy management is a new concept of clothing functionalization proposed in recent years. Thermal energy management refers to the use of clothing functionalization to enhance and improve the heat exchange between the human body and the environment, thereby improving the comfort of wearing clothing. Among the many thermal energy management methods, radiant cooling is an emerging thermal energy management method in recent years. By making the fabric surface have both high solar reflection effect and high atmospheric window emission performance, when people wear this functional clothing, the high solar reflection effect can reduce the incident solar energy, and at the same time, the high "atmospheric window" emission effect can emit the heat generated during body movement into outer space in the form of 8-13 micron thermal radiation, achieving heat dissipation and cooling effects.

[0003] To realize the radiation cooling function on the fabric surface, it is necessary to use dyes with radiation cooling effect, and the core of dyes is slurry with radiation cooling function.

[0004] In the prior art, the slurry that realizes the radiative cooling function is usually composed of two types of materials. The first type of material is a high refractive index filler, which requires the material itself to have a high refractive index. High refractive index materials can make clothing have a higher sunlight reflection performance, and at the same time, can ensure that the prepared dye has a higher hiding power. Among this type of filler, titanium dioxide is the most commonly used sunlight reflection filler with the best comprehensive performance.

[0005] As we all know, titanium dioxide has three crystal forms, namely rutile, anatase, and brookite. Among them, rutile titanium dioxide has the highest refractive index and the best reflection performance. However, high-purity rutile titanium dioxide is relatively expensive. As the main component of slurry, it is also the main component of production cost. If the use of titanium dioxide can be reduced, the cost can be effectively reduced.

[0006] The second type of material is emissive filler. Common emissive fillers are silica microspheres and glass microspheres. This type of material has good emissive performance in the 9.2-micron far-infrared band. The problem with the prior art is that it is difficult to unify low hiding power, low cost and high performance. On the one hand, high reflective performance requires a higher filler solid content in the fabric. Taking rutile titanium dioxide as an example, although high-solid content rutile titanium dioxide can improve its sunlight reflection performance, the fabric will incur high costs and is difficult to be competitive in the market. On the other hand, although fillers such as silica microspheres and glass microspheres have higher emissive performance, the refractive index of this type of material is too low. Increasing the content of emissive fillers will lower the overall refractive index of the filler and reduce the sunlight reflection effect of the fabric. In order to ensure the functionality of radiative cooling, it is necessary to increase the content of titanium dioxide, thus falling into a vicious circle.

[0007] Therefore, radiative cooling fabrics require a rare earth white dye slurry with a low titanium content while ensuring radiative cooling functionality. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a rare earth slurry for radiant cooling cloth and a preparation method thereof, so as to at least achieve the effects of low manufacturing cost of the slurry, high window emissivity and high reflectivity.

[0009] The objective of the present invention is achieved through the following technical solutions:

[0010] A rare earth slurry for radiant cooling fabric:

[0011] In parts by weight, the raw materials include 10-25 parts of aluminum oxide, 5-10 parts of barium oxide, 25-36 parts of niobium oxide, 13-20 parts of rare earth oxide, and 16-35 parts of titanium oxide.

[0012] Furthermore, the rare earth oxide is lanthanum oxide or cerium oxide.

[0013] Furthermore, the method for preparing the slurry comprises the following steps:

[0014] S1: mixing the aluminum oxide, niobium oxide, barium oxide, rare earth oxide and titanium oxide and crushing them;

[0015] S2: sintering the crushed powder at high temperature, and then quenching the sintered molten liquid in cold water to obtain a crude product powder;

[0016] S3: adding the crude product powder to a solvent for grinding to obtain A1 slurry with a particle size of 15-25 μm, A2 slurry with a particle size of 5-10 μm, and A3 slurry with a particle size of 0.3-0.7 μm;

[0017] S4: Mix the A1 slurry, A2 slurry and A3 slurry to obtain.

[0018] Furthermore, in step S2, the particle size of the crushed powder is 30-40 mesh.

[0019] Furthermore, in step S2, the sintering temperature is 360-1400°C;

[0020] Furthermore, in step S2, the sintering time is 4-4.5 hours.

[0021] Furthermore, in step S3, the particle size is a median particle size.

[0022] Furthermore, the weight ratio of the A1 slurry, the A2 slurry and the A3 slurry is 1:0.8-1.3:0.4-0.6.

[0023] Further, in step S3, the solvent includes water or butyl acetate;

[0024] And / or, the solid content of the A1 slurry, A2 slurry and A3 slurry is 30-40%

[0025] It is worth noting that the filler material used in this patent is an amorphous material with a high refractive index. The advantage of amorphous materials is that all materials have uniform properties, including refractive index, band gap, and emissivity. In the prior art, fillers with different functions are usually mixed as fillers. However, in actual effect, the concentrations of fillers with different functions are diluted, resulting in the performance of the fillers increasing and decreasing.

[0026] In the actual preparation process of amorphous materials, the content of each component is not randomly matched. Only when each component is mixed in a certain proportion can a uniform amorphous structure be formed, otherwise the second phase segregation and other results will appear. In actual operation, the most direct detection method is to wait for the raw materials to melt into a homogeneous solution, then take a small amount of molten liquid and pour it directly on the surface of the iron plate, let it cool naturally in the air, and observe whether the cooled droplet sample is as transparent as glass. Although aluminum oxide, niobium oxide and rare earth oxides are used as the main raw materials, amorphous materials with uniform properties can be obtained by formula regulation, however, the refractive index of this material is only about 1.8-2, which is relatively low. In the present invention, barium and titanium elements are additionally introduced into the system, and the refractive index can be further increased by this method, while maintaining the system with a higher band gap. We have successfully obtained a uniform amorphous material with a high refractive index by in-depth regulation of the formula ratio.

[0027] The beneficial effects of the present invention are:

[0028] 1. The slurry of the present invention has low raw material cost, high window emissivity and high reflectivity, and can be used to prepare coating products. The slurry of the present invention is green and environmentally friendly, and can be applied on the surface of fabrics, building exterior walls, roofs, and oil tanks to effectively reduce the surface temperature of objects.

[0029] 2. The "atmospheric window" emissivity of the slurry for the radiation cooling coating of the present invention is as high as 96%, while the reflection effect of ultraviolet-visible-infrared light is as high as 92%. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD diffraction spectrum of the powder material in the embodiment;

[0031] Figure 2 The slurry reflectivity test results in the embodiment;

[0032] Figure 3 These are photos of the precursor samples in Example 1 and Comparative Example 1 after natural cooling. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.

[0034] Example 1

[0035] Take 15 parts of aluminum oxide, 5 parts of barium oxide, 26 parts of niobium oxide, 16 parts of lanthanum oxide, and 30 parts of titanium oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh sieve to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the blocky precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder.

[0036] The precursor powder is loaded into a corundum crucible and heated in a melting furnace with stirring, wherein the heating program is: the first stage, the temperature range is 50-400 degrees, the time is 35 minutes; the second stage, the temperature range is 400-400 degrees for insulation, the time is 30 minutes; the third stage is 400-900 degrees, the time is 1 hour; the fourth stage is 900-1400 degrees, the time is 2 hours; the fifth stage is 1400 degrees constant temperature, the time is 4 hours; then the program is terminated. Among them, after the fifth stage is kept warm for 3 hours, the corundum stirring paddle is lowered into the liquid, and slowly stirred at a speed of 60 revolutions per minute for 30 minutes, and then the stirring paddle is lifted. After the heating program is completed, the liquid is directly poured into water for cold quenching, and the powder in the water is filtered to obtain the coarse powder.

[0037] Take a small amount of precursor powder, put it into the corundum crucible, and heat it in a melting furnace at a heating rate of 5 degrees per minute from room temperature to 1400 degrees, keep the constant temperature for 4 hours, and then pour the liquid on the surface of a 300x300x50 (mm) stainless steel plate while it is hot. The obtained droplet is naturally cooled in the air, and the obtained photo Figure 3 (left) shows that the sample is uniform and amorphous. The coarse powder was subjected to XRD test, and the results are as follows Figure 1 As shown, it can be seen from the results that the material structure is indeed an amorphous material.

[0038] A 40% coarse material powder solution was prepared, of which the dispersant content was 12%. The dispersant was BYK111 type dispersant, and the solvent was water. 10 kg of coarse material powder solution was put into a sand mill for sand grinding. The grinding ball particle size was 0.5 mm. The slurry particle size was tested once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size was obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.

[0039] The three slurries were mixed in a mass ratio of A1:A2:A3=1:1:0.5 to finally obtain a finished slurry.

[0040] Test method: For the reflection performance test, the slurry needs to be prepared into a coating sample for testing. The specific method is to take 30g of water-based acrylic resin with a solid content of 35%, 60g of finished slurry, add appropriate amount of water to adjust the viscosity of the coating, and evenly apply the coating on the surface of the aluminum sheet. After the resin is completely cured and dried, use a UV-visible-infrared spectrophotometer to test the reflection effect. The results are as follows: Figure 2 As shown, the average reflection effect can reach 92%. The emissivity data of the slurry was tested by the IR-1 hemispherical emissivity tester. At 25 degrees, the window emissivity at 8-14μm was measured to be 0.96, showing excellent emission performance.

[0041] Example 2

[0042] Take 20 parts of aluminum oxide, 10 parts of barium oxide, 36 parts of niobium oxide, 20 parts of cerium oxide, and 16 parts of titanium oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder.

[0043] The precursor powder is loaded into a corundum crucible and heated in a melting furnace with stirring, wherein the heating program is: the first stage, the temperature range is 50-400 degrees, the time is 35 minutes; the second stage, the temperature range is 400-400 degrees for insulation, the time is 30 minutes; the third stage is 400-900 degrees, the time is 1 hour; the fourth stage is 900-1400 degrees, the time is 2 hours; the fifth stage is 1400 degrees constant temperature, the time is 4 hours; then the program is terminated. Among them, after the fifth stage is kept warm for 3 hours, the corundum stirring paddle is lowered into the liquid, and slowly stirred at a speed of 60 revolutions per minute for 30 minutes, and then the stirring paddle is lifted. After the heating program is completed, the liquid is directly poured into water for cold quenching, and the powder in the water is filtered to obtain the coarse powder.

[0044] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate, and water is used in this embodiment). 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry of the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.

[0045] The three slurries were mixed in a mass ratio of A1:A2:A3=1:1.2:0.5 to finally obtain a finished slurry.

[0046] Test method: The coarse powder was subjected to XRD test. From the results, it can be seen that the material structure is indeed an amorphous material. For the reflection performance test, the slurry needs to be prepared into a coating sample for testing. The specific method is to take 30g of water-based acrylic resin with a solid content of 35%, 60g of finished slurry, add appropriate amount of water to adjust the viscosity of the coating, and evenly apply the coating on the surface of the aluminum sheet. After the resin is completely cured and dried, use a UV-visible-infrared spectrophotometer to test the reflection effect. The average reflection effect can reach 92%. The emissivity data of the slurry was tested by the IR-1 hemispherical emissivity tester. At 25 degrees, the window emissivity at 8-14μm was measured to be 0.95.

[0047] Comparative Example 1

[0048] Take 5 parts of aluminum oxide, 15 parts of barium oxide, 24 parts of niobium oxide, 25 parts of lanthanum oxide, and 30 parts of titanium oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh sieve to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the blocky precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder.

[0049] The precursor powder was placed in a corundum crucible and heated in a melting furnace at a rate of 5 degrees per minute from room temperature to 1400 degrees, and the temperature was kept constant for 4 hours. Then a small amount of liquid was poured onto a 300x300x50 (mm) stainless steel plate while hot. The obtained droplet was naturally cooled in the air. The obtained sample photo Figure 3 (Right) shows that crystallization occurs inside the sample.

[0050] It can be seen that if the ratio of each ingredient exceeds the range specified in the present invention, crystallization will occur inside the precursor material, and the coarse powder with crystallization phenomenon is not suitable for preparing radiation refrigeration materials because it will reduce the refractive properties of the material.

[0051] Take the samples of Example 1 and Comparative Example 1 (i.e. Figure 3 Zuohefu Figure 3 The samples on the right were tested respectively by ellipsometer to test the refractive index. The test results were as follows: the refractive index of the samples of Examples 1 and 2 was 2.5, while the refractive index of the sample of Comparative Example 2 was 2.0.

[0052] Comparative Example 2

[0053] Take 30 parts of aluminum oxide, 3 parts of barium oxide, 45 parts of niobium oxide, 10 parts of cerium oxide, and 10 parts of titanium oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder.

[0054] The precursor powder is loaded into a corundum crucible and heated in a melting furnace with stirring, wherein the heating program is: the first stage, the temperature range is 50-400 degrees, the time is 35 minutes; the second stage, the temperature range is 400-400 degrees for insulation, the time is 30 minutes; the third stage is 400-900 degrees, the time is 1 hour; the fourth stage is 900-1400 degrees, the time is 2 hours; the fifth stage is 1400 degrees constant temperature, the time is 4 hours; then the program is terminated. Among them, after the fifth stage is kept warm for 3 hours, the corundum stirring paddle is lowered into the liquid, and slowly stirred at a speed of 60 revolutions per minute for 30 minutes, and then the stirring paddle is lifted. After the heating program is completed, the liquid is directly poured into water for cold quenching, and the powder in the water is filtered to obtain the coarse powder.

[0055] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate, and water is used in this embodiment). 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry of the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.

[0056] The three slurries were mixed in a mass ratio of A1:A2:A3=1:0.8:0.5 to finally obtain a finished slurry.

[0057] Test method: The coarse powder is subjected to XRD test. The test results show that the material structure is a crystalline material. For the reflection performance test, the slurry needs to be prepared into a coating sample for testing. The specific method is to take 30g of water-based acrylic resin with a solid content of 35%, 60g of finished slurry, add appropriate amount of water to adjust the viscosity of the coating, and evenly apply the coating on the surface of the aluminum sheet. After the resin is completely cured and dried, use a UV-visible-infrared spectrophotometer to test the reflection effect. The reflection effect can reach 85%. The emissivity data of the slurry is tested by the IR-1 hemispherical emissivity tester. At 25 degrees, the window emissivity at 8-14μm is measured to be 0.90.

[0058] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A rare earth slurry for radiant cooling fabric, characterized in that: In parts by weight, the raw materials include 10-25 parts of aluminum oxide, 5-10 parts of barium oxide, 25-36 parts of niobium oxide, 13-20 parts of rare earth oxide, and 16-35 parts of titanium oxide; The method for preparing the slurry comprises the following steps: S1: mixing the aluminum oxide, niobium oxide, barium oxide, rare earth oxide and titanium oxide and crushing them; S2: sintering the crushed powder at high temperature, and then quenching the sintered molten liquid in cold water to obtain a crude product powder; S3: adding the crude product powder to a solvent for grinding to obtain A1 slurry with a particle size of 15-25 μm, A2 slurry with a particle size of 5-10 μm, and A3 slurry with a particle size of 0.3-0.7 μm; S4: mixing the A1 slurry, the A2 slurry and the A3 slurry to obtain; In step S2, the sintering temperature is 1400°C.

2. The slurry according to claim 1, characterized in that: The rare earth oxide is lanthanum oxide or cerium oxide.

3. The slurry according to claim 1, characterized in that: In step S2, the particle size of the crushed powder is 30-40 mesh.

4. The slurry according to claim 1, characterized in that: In step S2, the sintering time is 4-4.5 hours.

5. The slurry according to claim 1, characterized in that: In step S3, the particle size is a median particle size.

6. The slurry according to claim 1, characterized in that: The weight ratio of the A1 slurry, A2 slurry and A3 slurry is 1:0.8-1.3:0.4-0.

6.

7. The slurry according to claim 1, characterized in that: In step S3, the solvent includes water or butyl acetate.

8. The slurry according to claim 1, characterized in that: In step S4, the solid content of the A1 slurry, the A2 slurry and the A3 slurry is 30-40%.

Citation Information

Patent Citations

  • Preparation process of far-infrared powder

    CN103833335A

  • Cement-based radiation refrigeration dry powder paint, building coating and coating preparing method

    CN110105798A

  • Radiation refrigeration functional coating and application thereof

    CN110896639A

  • Preparation method of high-thermal-conductivity radiation refrigeration material

    CN116285183A